Larson's Musical Forces in Schlenker's Music Semantics - Mick de Neeve (Baltic International Yearbook of Cognition, Logic and Communication, 2023)
Larson’s musical forces of gravity, magnetism and inertia link music to metaphors of physical motion. Schlenker’s music semantics is based on similar physical world associations. Because Larson’s forces are about note movements towards harmonic stability, his framework implies note groupings at stable boundaries, given common cadential harmony. These groupings with forces assignments can then be viewed as musical events in Schlenker’s approach, and mapped to structure-preserving external (world) events as required for this author’s semantics. To this end, Schlenker’s truth definition, specifying when an event is ‘true of’ a musical expression, will be adapted. The synthesis amounts to what Schlenker argues for: a formal semantics of music, albeit limited to melodic lines confined to a single key.
Keywords: music; music semantics; semantics; syntax; musical forces